Stress and coping among surgical unit nurses of a teaching hospital - Laura de Azevedo Guido; Rodrigo Marques da Silva; Carolina Tonini Goulart; Raquel Einloft Kleinübing; Juliane Umann (Rev Rene)
This study aimed at identifying the stressors, the level of stress and coping strategies used by nurses in a surgical clinic of a university hospital. It is a cross-sectional study whose population consisted of nine nurses. Data were collected, between May and June 2005, through the Survey Form for Daily Activities and Coping Strategies Inventory. It was verified that activities related to personnel management were valued as the most stressful. Indicating a nurse in a state of alert for high levels of stress was valued like three medium levels and five with low level of stress. It was observed that solving problems was the most commonly used factor to face stress. Knowledge of the stressors and the ways of coping with them can help assist in the development of possible solutions to minimize their effects and become the most productive and less stressful aspect of the daily life.